2002
DOI: 10.1093/ps/81.9.1415
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fatty acid composition and thiobarbituric acid-reactive substances of broilers fed different cultivars of sorghum

Abstract: Two experiments were conducted to evaluate the production parameters, muscle fatty acid composition, and lipid stability of birds fed four different cultivars of sorghum. Experiment 1 used ruby red and valpo red, and Experiment 2 used kinsman and mason cultivars of sorghum. The basal diet was a corn, soy, and flax meal, and sorghum cultivars were substituted at 10 or 5% in Experiments 1 and 2. No significant difference was observed for BW, feed consumption or feed efficiency (P > 0.05). The total lipids were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 15 publications
2
35
0
1
Order By: Relevance
“…Thus, relatively high arachidonic acid content of WM is also an attractive nutritional quality factor. The difference in fatty acid composition is possibly due to dietary differences (Cherian et al, 2002) as well as due to the differences in feeding behavior between the breeds (Wattanachant et al, 2004). In addition, this study also showed that genetic strain is an important factor affecting fatty acid composition among samples at different production stages.…”
Section: Fatty Acid Compositionmentioning
confidence: 54%
“…Thus, relatively high arachidonic acid content of WM is also an attractive nutritional quality factor. The difference in fatty acid composition is possibly due to dietary differences (Cherian et al, 2002) as well as due to the differences in feeding behavior between the breeds (Wattanachant et al, 2004). In addition, this study also showed that genetic strain is an important factor affecting fatty acid composition among samples at different production stages.…”
Section: Fatty Acid Compositionmentioning
confidence: 54%
“…19 TBARS values have been reported to be 1.82 mg MDA kg −1 in breast and 2.58 mg MDA kg −1 in drumstick obtained from fresh broiler carcasses. 19 Cherian et al 20 Table 2). This is because of the high oxygen levels in the aerobic package.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, several other studies also indicated that the indigenous chicken meat such as KNC (Jeon et al, 2010;Jung et al, 2011;Jayasena et al, 2013c) and Hinai-jidori chickens (Rikimaru and Takahashi 2010) contained significantly higher content of arachidonic acid in their meat than CB. Differences in diet (Cherian et al, 2002) and feeding behavior between the breeds (Wattanachant et al, 2004) may be responsible for the differences in the fatty acid composition of lipid layers separated during DFDS preparation in addition to the breed effect. The fat layer of soup made with KNC showed 6 times higher content of DHA as that made with CB (Table 3).…”
Section: Fatty Acid Composition Of Lipid Layers Separated From Soupsmentioning
confidence: 99%